Effective study of the prolactin on cellular communication network factor 3 at the osteoporotic lactating Iraqi women’s - Rashid, Noora Bashar; Khalaf, Mustafa Saleam; Fayadh, Mohammed Amer; Mukhlif, Mustafa M (Edelweiss Applied Science and Technology, 2025)
Breastfeeding is a natural biological phenomenon that usually occurs in women after childbirth due to the elevated production of the hormone prolactin, which triggers the secretion of milk from the lobules in the breast to feed the newborn. This process is generally associated with mineral, vitamin, and protein deficiencies in the mother and entails significant physiological alterations. The main objective of the study was to assess the correlation between blood prolactin hormone levels, vitamin D3, and CCN3 protein concentrations in lactating and non-lactating females. Two groups were selected for this purpose: the first included lactating females only, and the second consisted of non-lactating females. Serum samples from all participants were tested for prolactin using radioimmunoassay, vitamin D3 by chemiluminescence enzyme immunoassay, and CCN3 protein by infiltration technique. According to the quantitative analysis, lactating females had significantly higher concentrations of prolactin hormone and CCN3 compared to non-lactating females, along with a decrease in vitamin D3. To the best of the authors’ knowledge, the present study reveals that the increase in prolactin hormone during lactation stimulates a protective response through the upregulation of CCN3 protein. This protein plays a crucial role in cellular signaling, enhancing bone structure, and protecting against complications such as osteoporosis, which may arise due to reduced vitamin D3 levels.